Pengembangan Lembar Kerja Siswa (LKS) Menggunakan Model CORE Untuk Memfasilitasi Kemampuan Komunikasi Matematis Siswa - Ali, Faqih Haidar; Novaliyosi; Setiani, Yani (Jurnal Ilmiah Soulmath : Jurnal Edukasi Pendidikan Matematika, 2023)
One of the concerns in mathematics education currently lies in the lack of use of learning media to support student success in training their mathematical communication skills. Based on these problems, this research aimed to create Student Worksheets using the Connecting, Organizing, Reflecting, and Extending (CORE) model that are feasible for use (valid and practical) and effective for facilitating students' mathematical communication skills. This research is part of a Research and Development (R & D) type of research which refers to the ADDIE development model (Analysis, Design, Development, Implementation, and Evaluation). It was administered at State Junior High School 12 Tangerang City, and the research subjects were students in class IX.8 for the 2022/2023 Academic Year with a total of 35 students. Validity data from validation sheets by material and media experts, practicality data from teacher and student response questionnaires, along effectiveness data from mathematical communication skills tests were used for data collection. The percentage validity of material and media experts is 81.1%, and 82.0% with very valid criteria. The practicality percentage of teacher and student response questionnaires was 82.7%, and 75.6% with very practical for teacher response and practical criteria for student response. The student completeness percentage is 78.1%, was declared effective with high criteria, so the student worksheets already facilitates mathematical communication skills. Thus, the student worksheet has been produced is feasible to use and effective in facilitating mathematical communication skills. Keywords: Student Worksheet, CORE Model, Mathematical Communication Skills.